Coated polymeric needles for rapid and deep intradermal delivery - Álvaro Cárcamo-Martínez; Qonita Kurnia Anjani; Andi Dian Permana; Ana Sara Cordeiro; Eneko Larrañeta; Ryan F. Donnelly (Elsevier, 2020)
Two groups of single polymeric needles (crosslinked Gantrez®S-97 and poly(ethylene glycol)) of different lengths (2 mm and 4.5 mm) with defined base widths were fabricated and tested in terms of their mechanical strength and insertion abilities using two skin models (Parafilm® and porcine skin). For the shorter needles, application of an axial force (32 N) resulted in a height reduction of approximately 80%. Nonetheless, around 80% of total needle length was successfully inserted in both skin models. Optical coherence tomography showed that base width highly impacted insertion capabilities of the longer needles as only the thicker one (0.922 mm width at base) inserted into porcine skin. Additionally, needles were coated with rhodamine B and inserted into porcine skin. In comparison to a control, penetration depth of the model drug increased 2-fold for short and 4.5-fold for long needles, respectively. Moreover, quantification across skin sections showed that shorter needles delivered 10 μg of the compound in a depth of 1.5-2.0 mm while long needles were capable of delivering 5 μg into even deeper skin layers (2.0-3.0 mm), confirming the potential of coated polymeric needles for rapid and deep intradermal delivery.